2012
DOI: 10.1590/s1981-81222012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Paisagens e etnoconhecimentos na agricultura Ticuna e Cocama no alto rio Solimões, Amazonas

Abstract: Resumo: As unidades de paisagem na agricultura dos povos Ticuna e Cocama, no alto rio Solimões, são caracterizadas por arranjos produtivos e formas de gestão dos recursos naturais. Caracterizar essas práticas de base agroecológica, os resultados paisagísticos e as possibilidades de sua aplicabilidade regional foram os objetivos dessa pesquisa, realizada em duas localidades: Novo Paraíso, na ilha do Bom Intento, e Nova Aliança, ambas no município de Benjamin Constant, Amazonas. A organização social e econômica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 1 publication
0
2
0
7
Order By: Relevance
“…Behind the "restingas" the terrain declines smoothly, delimiting lower areas, constituting the "chavascais" (class 65 -70 m) [30]. When the depression in "chavascal" is more pronounced, the "poço" [3] forms an important part of the landscape recognized by local family farmers, characterized by maintaining water depth even in the dry season. "Chavascal" and "poços" guarantee family farmers access to the water used for manual irrigation of those cultivated species most susceptible to water stress in the summer, such as vegetables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behind the "restingas" the terrain declines smoothly, delimiting lower areas, constituting the "chavascais" (class 65 -70 m) [30]. When the depression in "chavascal" is more pronounced, the "poço" [3] forms an important part of the landscape recognized by local family farmers, characterized by maintaining water depth even in the dry season. "Chavascal" and "poços" guarantee family farmers access to the water used for manual irrigation of those cultivated species most susceptible to water stress in the summer, such as vegetables.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies in the Brazilian Amazon have demonstrated the fundamental role of family agriculture in the conservation of agrobiodiversity, that is, in maintaining the evolutionary dynamics of cultivated species, as well as the complex agroecosystems of floodplain and "terra firme" rain forest [1] [2] [3]. The authors argue that the production strategies and techniques used by family farmers make it possible to generate a sufficient diversity of products to meet the food demands of the families, maintaining a high level of agricultural diversity, especially in the Amazonian floodplains.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos recentes destacam os altos níveis de agrobiodiversidade favorecidos pelo manejo destas áreas (EMPERAIRE e ELOY, 2008;PEDROSO JUNIOR et al, 2008;PADOCH e PINEDO-VASQUEZ, 2010;LIMA et al, 2012;LIMA et al, 2013;NODA et al, 2012;. Estes sistemas são os mais difundidos entre as diversas famílias de pequenos agricultores (PEDROSO JUNIOR et al, 2008;RICHERS, 2010) onde incluem-se diferentes grupos de agricultores familiares (indígenas, ribeirinhos, assentados, colonos, etc.)…”
Section: Introductionunclassified
“…Estudos recentes destacam os altos níveis de agrobiodiversidade favorecidos pelo manejo destas áreas (EMPERAIRE e ELOY, 2008;PEDROSO JUNIOR et al, 2008;PADOCH e PINEDO-VASQUEZ, 2010;LIMA et al, 2012;LIMA et al, 2013;NODA et al, 2012;. Estes sistemas são os mais difundidos entre as diversas famílias de pequenos agricultores (PEDROSO JUNIOR et al, 2008;RICHERS, 2010) onde incluem-se diferentes grupos de agricultores familiares (indígenas, ribeirinhos, assentados, colonos, etc.)…”
Section: Introductionunclassified